Foregrounding Sociomaterial Practice in Our Understanding of Affordances: The Skilled Intentionality Framework - van Dijk, Ludger; Rietveld, Erik (Frontiers in Psychology, 2017)
Social coordination and affordance perception always take part in concrete situations in real life. Nonetheless, the different fields of ecological psychology studying these phenomena do not seem to make this situated nature an object of study. To integrate both fields and extend the reach of the ecological approach, we introduce the Skilled Intentionality Framework (SIF) that situates both social coordination and affordance perception within the human form of life and its rich landscape of affordances. We argue that in the human form of life the social and the material are intertwined and best understood as sociomateriality. Taking the form of life as our starting point foregrounds sociomateriality in each perspective we take on engaging with affordances. Using ethnographical examples we show how sociomateriality shows up from three different perspectives we take on affordances in a real-life situation. One perspective shows us a landscape of affordances that the sociomaterial environment offers. Zooming in on this landscape to the perspective of a local observer, we can focus on an individual coordinating with affordances offered by things and other people situated in this landscape. Finally, viewed from within this unfolding activity, we arrive at the person’s lived perspective: a field of relevant affordances solicits activity. The Skilled Intentionality Framework offers a way of integrating social coordination and affordance theory by drawing attention to these complementary perspectives. We end by showing a real-life example from the practice of architecture that suggests how this situated view that foregrounds sociomateriality can extend the scope of ecological psychology to forms of so-called “higher” cognition.